2000
DOI: 10.1523/jneurosci.20-17-06326.2000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Presynaptic Ca2+ Influx and Transmitter Release Kinetics during Facilitation at the Inhibitor of the Crayfish Neuromuscular Junction

Abstract: The inhibitory synapse of the crayfish neuromuscular junction was used to examine mechanisms underlying the F2 component of synaptic facilitation. Because previous studies have shown accelerated transmitter release during facilitation, we examined whether an activity-dependent plasticity in I Ca could underlie this acceleration. We established that fluorescent transients generated by Magnesium Green can resolve small differences in presynaptic Ca 2ϩ influx that correlate with changes in IPSC waveform. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 41 publications
4
9
0
Order By: Relevance
“…The frequency dependent desynchronization we describe appears similar to the activity-induced prolongation of the phasic vesicle release rate at the calyx of Held (Fedchyshyn and Wang, 2007; Scheuss et al, 2007), hippocampus (Diamond and Jahr, 1995), cortex (Boudkkazi et al, 2007), and other synapses (Auger et al, 1998; Vyshedskiy et al, 2000; Waldeck et al, 2000). Yet activity-dependent desynchronization at CF synapses does not recruit delayed release, as described at other synapses following repetitive activation (Atluri and Regehr, 1998; Lu and Trussell, 2000; Hefft and Jonas, 2005; Iremonger and Bains, 2007).…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The frequency dependent desynchronization we describe appears similar to the activity-induced prolongation of the phasic vesicle release rate at the calyx of Held (Fedchyshyn and Wang, 2007; Scheuss et al, 2007), hippocampus (Diamond and Jahr, 1995), cortex (Boudkkazi et al, 2007), and other synapses (Auger et al, 1998; Vyshedskiy et al, 2000; Waldeck et al, 2000). Yet activity-dependent desynchronization at CF synapses does not recruit delayed release, as described at other synapses following repetitive activation (Atluri and Regehr, 1998; Lu and Trussell, 2000; Hefft and Jonas, 2005; Iremonger and Bains, 2007).…”
Section: Discussionsupporting
confidence: 57%
“…It is harder, however, to predict the significance of desynchronized vesicle release on the millisecond timescale. This may explain why the physiological consequences of desynchronized release have remained largely unexplored, despite the demonstration that this form of release occurs throughout the brain (Diamond and Jahr, 1995; Auger et al, 1998; Vyshedskiy et al, 2000; Waldeck et al, 2000; Fedchyshyn and Wang, 2007; Scheuss et al, 2007). It is proposed that regulation of release latency on the millisecond timescale provides a temporal code that may enrich the storage capacity of neural networks (Boudkkazi et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known regarding whether the various temporal components of neurotransmission show activity‐dependent plasticity when synapses are presented with more physiological stimuli such as high frequency trains. Indeed, when this issue was investigated in non‐mammalian synapses using other protocols such as paired‐pulse stimuli or trains, it was demonstrated that SD could be modified under appropriate conditions (Vyshedskiy et al 2000; Waldeck et al 2000). At the calyx of Held‐MNTB synapse, increases in both AP latency and EPSC onset have also been observed following prolonged tetanic stimulation (Habets & Borst, 2005; Kim et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, recent evidence from other synapses, including the goldfish Mauthner cell synapse and crayfish NMJ, suggests that synaptic delay is modifiable. Paired‐pulse depression in the Mauthner cell synapse is associated with a prolongation in synaptic delay (Waldeck et al 2000), while facilitation at the crayfish NMJ leads to an activity‐dependent shortening in synaptic delay (Vyshedskiy et al 2000). These studies raise the possibility that the temporal components of neurotransmitter release, including synaptic delay, may undergo changes, either in parallel with or independently of, changes in synaptic strength.…”
mentioning
confidence: 99%
“…Vyshedskiy et al . (2000) showed that increases in the basal intracellular [Ca 2+ ] level reduced the delay and peak time of synaptic current at a tonic inhibitory synapse.…”
Section: Resultsmentioning
confidence: 99%